Efektifitas Pengembangan Pembelajaran Senam Lantai Berbasis Digital Pada Materi Round Back Roll - zulbahri, zulbahri; Madri, Madri; Arnando, Muhammad; Sepriadi, Sepriadi; Sasmitha, Weny; Amra, Frizki (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
Preliminary research results show that conventional gymnastics learning and online media in the form of e-learning at the Department of Physical Education, Faculty of Sports Science, have not been able to produce students' gymnastic skills to the fullest, especially for round back roll movements. Therefore it is necessary to design a digital-based exercise learning device with the aim of making it easier for students to understand learning and lecture material, specifically for round back roll material. This research was conducted to produce e-RPS and e-Modules for digital-based gymnastics learning that meet valid, practical and effective criteria for students of the Department of Sports Education, Faculty of Sports Science. Operationally, the design of the e-RPS and e-Module is manifested in the form of learning links and also in the form of pdfs and videos. This research is Research and Development (R&D). The design development process refers to the development of the Ploom & Nieveen model which consists of the preliminary research, prototyping phase, and assessment phase. Field trials were carried out at the Department of Sports Education, Faculty of Sports Science. The results of the study were obtained by the level of effectiveness of the development of digital-based floor gymnastics learning on round back roll material with a gain n score of 60.73%, with a moderately effective category.